"That's Where the Arguments Come in": A Qualitative Analysis of Booster Sessions following a Brief Intervention for Drug Use and Intimate Partner Violence in the Emergency Department - Esther K. Choo; Chantal Tapé; Kimberly M. Glerum; Michael J. Mello; Caron Zlotnick; Kate Morrow Guthrie (SAGE Publishing, 2016)
Although booster phone calls have been used to enhance the impact of brief interventions in the emergency department, there has been less number of studies describing the content of these boosters. We conducted a qualitative analysis of booster calls occurring two weeks after an initial Web-based intervention for drug use and intimate partner violence (IPV) among women presenting for emergency care, with the objective of identifying the following: progress toward goals set during the initial emergency department visit, barriers to positive change, and additional resources and services needed in order to inform improvements in future booster sessions. The initial thematic framework was developed by summarizing codes by major themes and subthemes; the study team collaboratively decided on a final thematic framework. Eighteen participants completed the booster call. Most of them described a therapeutic purpose for their drug use. Altering the social milieu was the primary means of drug use change; this seemed to increase isolation of women already in abusive relationships. Women described IPV as interwoven with drug use. Participants identified challenges in attending substance use treatment service and domestic violence agencies. Women with substance use disorders and in abusive relationships face specific barriers to reducing drug use and to seeking help after a brief intervention.